Concentration by membrane separation processes of a medicinal product obtained from pineapple pulp - Francisco Luiz Gumes Lopes; João Baptista Severo Júnior; Roberto Rodrigues de Souza; Daniela Diniz Ehrhardt; José Carlos Curvelo Santana; Elias Basile Tambourgi (Brazilian Archives of Biology and Technology, 2009)
The concentration of pineapple juice is needed to retain the bromelain activity and to standardize the composition and proteolytic activity. Thus, this work aimed to obtain a pure bromelain extract from the Ananas comosus L. Merril juice by membrane separation process. A 2² experimental planning was used to study the influence of pH and transmembrane pressure on the activity recovery by micro-filtration using a plain membrane. In second step, this enzyme was purified by the ultra-filtration using a 10 kDa millipore kit. The best operation condition to bromelain concentration using the plain membrane was at pH 7.5 and transmembrane pressure of 0.05 bar, while 85% of bromelain activity was recovered. Ultra-filtration retained 100% of proteolytic activity and concentrated in 10 fold the bromelain extract. SDS-PAGE electrophoresis showed that the ultra-filtrated had high purity and the bromelain from A. comosus pulp had a molecular weight of 24.5 kDa. A concentração do suco de abacaxi é necessária para manter a atividade da bromelina e padronizar a composição e atividade proteolítica. Assim, este trabalho objetivou a obter um extrato de bromelina pura do suco do Ananas comosus L. Merril por processos de separação por membranas. Um planejamento experimental do tipo 2² foi feito para estudar a influência do pH a da pressão transmembranar sobre a recuperação da atividade por micro-filtração usando uma membrana plana. Em uma segunda etapa, purificou-se a enzima alvo por ultra-filtração usando um "kit millipore" de 10 kDa. A melhor condição para a concentração da bromelina foi a pH 7,5 e pressão transmembranar de 0,05 bar, onde 85% da atividade da bromelina foi recuperado. A ultra-filtração manteve 100% da atividade proteolítica e concentrou em 10 vezes o extrato de bromelina. A eletroforese via SDS-PAGE mostrou que o ultra-filtrado teve alta pureza e a bromelina da polpa do Ananas comosus tem um peso molecular de 24.5 kDa.